Verification of autoclave effectiveness using chemical indicators in a dental environment - Morocho Morocho, Robinson A. (2024)
Objectives: Verify the effectiveness of autoclaves using chemical indicators in the pre-professional clinics of a higher institution. Materials and methods: An observational study was carried out in pre-professional clinics of a higher training institution for dentists in the city of Cuenca, Ecuador. Ninety-four readings with chemical indicators were used in two functional autoclaves distributed among three clinics. The evaluation was based on the 3M® control and chemical integrator 3M® Attest® 1243B, with results classified as “Accepted” or “Rejected.” The indicators were placed in various locations within the autoclaves and monitored for four weeks, at two specific times of the day. Results: Of the 94 chemical indicators used, 63.8% resulted in “Accepted,” evidencing the effectiveness of the sterilization, while 36.2% were classified as “Rejected,” indicating unsatisfactory sterilizations. The distribution of results varied between clinics and according to the location of the indicators within the autoclaves. Conclusions: The study concludes that, although most autoclave sterilization cycles in pre- professional clinics are effective, there is significant room to improve the effectiveness of these procedures. The location of chemical indicators within the autoclave influences sterilization results, suggesting the importance of optimizing instrument placement to ensure uniform and complete sterilization.